Innowacje w pracy socjalnej z osobami z niepełnosprawnością = Innovations in social work with people with disabilities - Korlak-Łukasiewicz, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the last half-century, there has been a revolution in the way contemporary society perceives supports, and treats people with disabilities, and interacts with them. The previous models of working with such people used in social work have been replaced with new, innovative approaches. Professional social workers will have to face the new challenge consisting in the right of people with disabilities to self-determination.
Keywords: innowacja; niepełnosprawność; praca socjalna; innovation; disability; social work